Precise Localization of the Subsolid Lesion by Colour Marking under CT-Guided Control before Video-Assisted Surgery Resection: A Case Report - Vladimír Červeňák; Zdeněk Chovanec; Jan Resler; Tomáš Hanslík; Alena Berková; Ondřej Bílek; Klára Novosádová; Viktor Weiss; Jiří Vaníček (Case Reports in Oncology)
Introduction: Lung cancer is one of the leading causes of death worldwide. Lung lesions, often discovered incidentally on chest CT, pose a diagnostic challenge due to their diverse etiology, including both benign and malignant nature. A key step in the assessment of these lesions is the evaluation of their morphological features in the CT image, size, and behavior over time. Nodules are divided into solid and subsolid according to their density. When surgical resection is necessary, solid lesions are palpable peroperatively, whereas subsolid lesions may be unidentifiable by palpation, and their precise localization is difficult. To spare patients from extensive surgery such as thoracotomy, it is advantageous to use one of the methods of preoperative marking of these lesions. Best practices include marking with mixtures containing patent blue and contrast agents, applied under CT guidance. This method allows accurate visualization of the localization of the lesion, which facilitates their resection by minimally invasive video-assisted surgery (VATS). Case Presentation: A 51-year-old female patient was found to have a subsolid lesion in the right lung during a routine follow-up CT scan of the lung for a history of malignant melanoma. The lesion was followed for 4 years and showed slow size progression and change from a pure ground glass nodule to a subsolid nodule. Due to the persistence of the nodule, change in morphology, and size progression, the patient was indicated for surgical resection. Using preoperative labeling with a mixture of blue dye and contrast agent, the nodule was successfully located and sublobary VATS resected. Conclusion: The color marking allowed accurate identification of the subpleurally located lesion, which would otherwise have been unvisualized and intangible, thus minimizing the need for more extensive surgery. This case highlights the key role of color marking in increasing resection success and surgical safety, particularly in small and subsolid nodules.